Validating the use of a smartphone app for remote administration of a fear conditioning paradigm. (December 2019) - Purves, K.L.; Constantinou, E.; McGregor, T.; Lester, K.J.; Barry, T.J.; Treanor, M.; Sun, M.; Margraf, J.; Craske, M.G.; Breen, G.; Eley, T.C.
Abstract: Fear conditioning models key processes related to the development, maintenance and treatment of anxiety disorders and is associated with group differences in anxiety. However, laboratory administration of tasks is time and cost intensive, precluding assessment in large samplesnecessary for the analysis of individual differences. This study introduces a newly developed smartphone app that delivers a fear conditioning paradigm remotely using a loud human scream as an aversive stimulus. Three groups of participants (total n = 152) took part in three studies involving a differential fear conditioning experiment to assess the reliability and validity of a smartphone administered fear conditioning paradigm. This comprised of fear acquisition, generalisation, extinction, and renewal phases during which online US-expectancy ratings were collected during every trial with evaluative ratings of negative affect at three time points. We show that smartphone app delivery of a fear conditioning paradigm results in a pattern of fear learning comparable to traditional laboratory delivery and is able to detect individual differences in performance that show comparable associations with anxiety to the prior group differences literature. Highlights: A smartphone app reliably delivers a differential fear conditioning paradigm using an aversive human scream. Within-person associations of fear conditioning between laboratory and app delivery do not differ from those across time. App-based administration is able to detect individual differences in anxiety related processes. Fear conditioning data can be collected with minimal financial and time cost.